Integrated 21st Century Science, Technology, Engineering, Mathematics (STEM) Education Through Robotics Project-Based Learning - Hussin, Hanipah; Pang, Yee Jiea; Raja Rosly, Raja Norhafiza; Omar, Siti Rohana (GIAP Journals, 2019)
Purpose of the study: To propose a new framework on integrated 21st century STEM education through Robotics Project-based Learning, and secondly, to outline a Robotics Project-based Learning curriculum in the perspective of integrated 21st century STEM education. Methodology: Content analysis was carried out to design a new framework. Secondary data collection technique was used. Main Findings: The proposed framework can identify itself with each STEM curriculum in Science, Technology, Engineering and Mathematics. Educational robotics as a tool to integrate the fours discipline through project-based learning. Applications of this study: The proposed framework is applicable in 21st century learning environment using studentcentered approach. 21st century skills are enhanced through collaboration, creativity, critical thinking and communication while students carry out robotics project-based learning. Novelty/Originality of this study: A new pedagogy of STEM integration in Malaysia education system. Hands-on and minds-on activities through robotics project-based learning promote higher order thinking in students.